Effect of using different packaging films on the texture and weight of enzvmatically peeled pommelo (citrus grandis) segments during low temperature storage. - Aziz, A. G.; Osman, Azizah; Ghazali, H. M.; Abdul Rahman, Russly (2001)
The effect ofusing different packaging films during storage of enzyme peeled pommelo segments at 7±loC; 90-95% RH on segments firmness (compression force), toughness (shearing force) and fluid loss (dehydration) during storage were studied. Pommelo fruit segments were placed in polystyrene tray and wrapped with PVC films of different thicknesses (10 and 14pm). The unwrapped samples served as control. The dry-pack unpasteurized pommelo segments were stored at 7±1"C; 90-95% RH and changes in the physical characteristics were analysed at one day intervals for a duration of seven days. Generally, changes in the physical characteristics were delayed in samples wrapped in packaging films as compared to the control. Samples wrapped with PVC loss less fluid compared to the control which turn drier and drier during the storage study for one week On the other hand, samples wrapped with PVC 14pm thickness loss less fluid than samples wrapped with PVC 10 um thickness during the study. Samples wrapped with PVC remain firm and moist throughout the study while the control became dry and tough. Generally, segments wrapped with PVC 14Wn thickness remained more fresh and had a very good shiny appearance compared to the other samples wrapped with PVC 10um thickness film.